2007
DOI: 10.1109/tasc.2007.899119
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Vortex Paths in HTS

Abstract: A random walk model of the vortex paths in high temperature superconductors is investigated for different relative densities of -axis, -plane and point pinning defects. The model suggests an origin for some of the more unusual features seen in the field angle dependence of the critical current. It also predicts greater noise in critical currents for fields parallel to the plane of the dominant pinning defects and anomalous behavior of -values. The random walk model also suggests an alternative form for the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…It is difficult to foresee how a deterministic model would ever predict a J c peak which is not aligned with the direction of correlated pinning, but this comes quite naturally from Equation (3b). Further examples of the use of these equations to explain J c () from complex pinning structures are given in [7][8][9][10]26,27]. Table 1.…”
Section: Out-of-plane Field Angular Dependence Of J C Under Maximum Lmentioning
confidence: 99%
See 3 more Smart Citations
“…It is difficult to foresee how a deterministic model would ever predict a J c peak which is not aligned with the direction of correlated pinning, but this comes quite naturally from Equation (3b). Further examples of the use of these equations to explain J c () from complex pinning structures are given in [7][8][9][10]26,27]. Table 1.…”
Section: Out-of-plane Field Angular Dependence Of J C Under Maximum Lmentioning
confidence: 99%
“…In earlier publications we derived Equations (3) by directly modeling the shape of the vortex path as a directed random walk [7,8]. That is for a peak centered in the y-direction, we modeled an arbitrarily chosen vortex as a finite set of m steps in the y-direction, giving say,…”
Section: Field Angle Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that BZO nanoparticle inclusions are able to create a more isotropic J c (θ ) profile [16]. In this paper, we investigate the role of the BZO nanoinclusions on the J c (θ ) dependencies by interpreting the respective data within the framework of the vortex path model [17][18][19]. In this statistical mechanical approach, the J c (θ ) curves may be decomposed into a set of distinct contributions that may be traced back to the particular microstructural features of the sample.…”
Section: Introductionmentioning
confidence: 99%